Integration of Psychosocial Assistance and Sharia Financial Literacy to Improve the Capacity of Islamic Students in Self-Management and Financial Planning - Mayadina Rohmi Musfiroh; Zahrotun Nafisah; Ahmad Fauzan; Amrina Rosyada (Universitas Nurul Jadid, 2025)
Psychosocial support among students is urgent because low mental health literacy can have an impact on mental and emotional health disorders. The lack of sharia-based financial planning literacy in students can create double vulnerabilities both managerial and psychological that have a direct impact on mental health. The integration of psychosocial support, mental health literacy, sharia-based financial planning literacy, and adolescent identity search forms a protective mechanism that simultaneously strengthens family resilience. This community service using psychosocial guidance and structured sharia-based financial planning literacy session methods that invite participants to explore the challenges of today's families and students, understand the order of personal values, recognize their strengths and weaknesses, and how students can plan their finances from an early age, held at the An-Nahdloh Islamic boarding school, Selangor Malaysia. Data collection was carried out through pre and post-test assessments, including observations, interviews and questionnaires to measure the level of understanding of personal conditions and financial literacy. The result of this service is that 85% of students increase their understanding; have a clear self-concept, have values that are a guideline for life and increase their capacity in terms of financial planning based on sharia principles. Psychosocial support as an external stimulus serves to optimize adolescent mental health literacy, which provides a cognitive scheme to manage emotional turmoil during the identity search crisis phase to remain oriented towards adaptive values. The presence of sharia-based financial planning literacy complements the process by providing an ethical-practical framework in resource management that is in line with the principles of monotheism, thereby reducing financial and existential conflicts which ultimately create functional synergy between family members as the main indicator of comprehensive family resilience.